Information Literacy in Brazil - Capinzaiki Ottonicar, Selma Leticia [UNESP]; Feres, Gloria Georges [UNESP]; Kurbanoglu, S.; Spiranec, S.; Grassian, E.; Mizrachi, D.; Catts, R. (Springer, 2014)
The Brazilian government focuses on the economy, thus national education policy is on the back burner, receiving less financial resources. This increases educational problems. Economic development occurs when information literacy is considered important; however we must consider multiple factors such as human and social development which is the outcome of building knowledge. This paper aims to investigate how information literacy is treated in Brazil by means of an in-depth literature review about this topic in the education and policy field and to discuss the current situation regarding initiatives that stimulate learning and effective citizenship. Afterwards, there is a description of the historical and theoretical aspects of information literacy studies between 2000 and 2013. The article contributes to the elaboration of that topic and it develops the building and dissemination of knowledge around the country.
Keywords: Information literacy; learning; nation development